2014
DOI: 10.1177/0194599814544881
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis and the Tonsils: A Review of Management

Abstract: Lack of evidence currently prevents firm conclusions, but the following is recommended: (1) Use reliable methods for halitosis diagnosis and confirmation of tonsillar etiology. Initial treatment such as tongue scraping is useful to rule out oral halitosis. (2) Tonsillar procedures are contraindicated in: subjective halitosis, non-tonsillar etiology, or if medical management resolves halitosis. (3) Where indicated and where facilities permit, less invasive techniques such as laser cryptolysis may be preferable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 44 publications
0
20
0
3
Order By: Relevance
“…Previous reports have suggested that the most common cause of extraoral halitosis is the tonsils [ 11 , 12 ], and chronic tonsillitis is the actual cause of idiopathic halitosis in most cases [ 13 ]. It has also been reported that about 3% of all halitosis are secondary to pathology of the palatine tonsils [ 14 ]. The palatine tonsils continuously sample antigens from inhaled air, foods, and the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that the most common cause of extraoral halitosis is the tonsils [ 11 , 12 ], and chronic tonsillitis is the actual cause of idiopathic halitosis in most cases [ 13 ]. It has also been reported that about 3% of all halitosis are secondary to pathology of the palatine tonsils [ 14 ]. The palatine tonsils continuously sample antigens from inhaled air, foods, and the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic subjective halitosis (Type 5) is known as a halitosis complaint without objective confirmation by others or by halitometer measurement [3]. That is, the patient believes there is halitosis, but no odor is clinically detectable [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Las halitosis de origen oral serán más detectables al exhalar por la boca, en cambio, aquellas que sean consecuencia de patología rinosinusal serán más detectables al exhalar por la nariz. Otras causas de halitosis pueden ser igualmente detectables tanto al exhalar por la boca como por la nariz 20 . Dentro de las ventajas de este examen se encuentra que es barato, no requiere equipamiento y permite reconocer un amplio rango de olores.…”
Section: Clasificaciónunclassified
“…Respecto a la tonsilolitiasis, durante muchos años se ha considerado una indicación relativa de amigdalectomía cuando ésta presenta un impacto en la calidad de vida de los pacientes. Sin embargo, en los últimos años, nuevas técnicas como la ablación por radiofrecuencia controlada por temperatura y la criptolisis amigdalina asistida con láser CO 2 han demostrado ser igual de efectiva que la amigdalectomía en el manejo de la halitosis asociada a la tonsilolitiasis, con menor dolor posoperatorio y menor riesgo de sangrado 20,41,42 . De éstas últimas, la criptolisis amigdalina asistida con láser CO 2 demostró tener menor dolor posoperatorio, menor riesgo de sangrado y progresión más rápida a una dieta habitual 43 .…”
Section: Tratamientounclassified
See 1 more Smart Citation